Factor influencing online shopping behavior through e-commerce: an extension of TPB with perceived enjoyment and trust - Suresh Kumar; Dian Permatasari (President University, 2022)
Facing the fierce completion in online shopping in Indonesia, this study aims to find out the drivers to increase online shopping behavior through purchase intention, attitude, subjective norms, perceived behavior control, perceived enjoyment, and trust. This study applied a quantitative approach with a survey as the method and gathered 373 samples in Greater Jakarta as the place of study. Looking at the complexity of the relationship, the data were analyzed using structural model. This study reveals that to increase the purchase intention of customers companies must consider perceived enjoyment, along with attitude, subjective norm, and perceived behavioral control. In addition, the purchase intention is the best driver to increase the shopping behavior through online among customers. However, trust was rejected in this study. This study also provides implications for managers and future directions based on the limitations of this study.